FORMATION OF INTESTINAL BIOCOENOSIS IN CHILDREN WITH BREAST AND ARTIFICIAL FEEDING - I.N. Zakharova; E.N. Surkova; Yu.A. Dmitriyeva; L.V. Begiashvili (Вопросы современной педиатрии)
Authors analyzed main stages of formation of intestinal biocoenosis in children with breast and artificial feeding. They presented principal risk factors of disorders of normal biocoenosis forming in infant. Advantages of administration of bifidus bacteria strain BB12 in children with artificial feeding are presented. Authors described proper experience of children’s feeding with adopted milk mixture. It was shown that an influence of mixture on the restoration of intestinal biocoenosis and formation of colonialist resistance of infants’ gastrointestinal tract is comparable to that one during breast feeding.Key words: infants, feeding, intestinal biocoenosis.(Voprosy sovremennoi pediatrii — Current Pediatrics. 2010;9(2):103-108)